Effect of desensitization using bioactive glass, hydroxyapatite, and diode laser on the shear bond strength of resin composites measured at different time intervals: An In vitro Study - Timsi Gupta; Shruthi Nagaraja; Sylvia Mathew; Indiresha H Narayana; K S Madhu; K Dinesh (Wolters Kluwer Medknow Publications, 2017)
Background: Dentin desensitizers may change the properties of smear layer and have adverse effects on the bonding performance of adhesive systems. Aim: The aim of this study was to compare the effect of bioactive glass (BG), hydroxyapatite, and diode laser desensitization on shear bond strength of resin composites to dentin at different time intervals. Materials and Methods: Seventy-two caries-free maxillary premolars were selected. Buccal surfaces were flattened to expose dentin. Teeth were divided into four groups (Groups 1, 2, 3, and 4) according to treatment modality (control with no pretreatment, Sensodyne Repair and Protect, Teethmate Desensitizer, diode laser). Bonding was performed using self-etch adhesive followed by composite buildup. Universal testing machine was used to determine shear bond strengths immediately after bonding, after 3 months, and 5 months storage in artificial saliva. Results: Pretreatment with BG and hydroxyapatite desensitizers increased, whereas diode laser decreased mean shear bond strength of composite to dentin as compared to control group. No statistical significant difference in shear bond strength values was seen in groups after storage. Conclusion: Desensitizing toothpastes incorporating remineralizing agents not only occluded open dentinal tubules but also increased shear bond strength of composite to dentin.